SYARI'AH MOVEMENTS IN COMPARASION: SOUTH SULAWESI AND WEST JAVA PROVINCE - Marom, Ahmad Anfasul (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2011)
This paper will examine the rise of perda syari'ah (syari'ah regional regulations) in contemporary Indonesia. Since the fall of Soeharto, the muslim politics has reemerged in the national politics constellation. From 1999 to 2002 three Islamic political parties (PPP, PBB, and PK) insisted on proposing to reinsert the seven words of the Jakarta Charter into the amendment of 1945 Constitution. They intensively strived for them through the inside of parliament. In the same time, their efforts were also fully supported by the Islamic radicalism organization from the outside building such as HTI (Liberation Party) and MMI (Council of Indonesian Jihad Fighters). lf they previously insisted to implement syari'ah in state level, now they attempted to have it from a local region. This can be witnessed from the application of syari'ah regional regulation (perda syari'ah) in some Muslim-majority districts such as Bulukumba, Gowa, Maros, Lombok, Pamekasan, Cianjur, Indramayu, Tasikmalaya, Padang, Banjarmasin, and Nanggro Aceh Darussalam. This study tries to compare two Muslim majority provinces (South Sulawesi and West Java) which have applied perda syari'ah since 2001.